Intensity and competitiveness of land use at regional level - Kucher, Anatoliy (Turystyka i Rozwój Regionalny, 2016)
The purpose of the research is to evaluate the competitiveness of land use of agricultural enterprises in regions of Ukraine and impact on it of level of intensity. As result of investigation it was identified the economic substance of the competitiveness of land use of agricultural enterprises; proposed to identify potential and actual level of competitiveness of land use of agricultural enterprises. It is proposed and tested the scientific and methodical approach to rating evaluation of the competitiveness of land use of agricultural enterprises in regions.